2021
DOI: 10.1109/lnet.2021.3066536
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Probability of Message Delivery Over Ever-Changing Communication Scenarios in Tactical Networks

Abstract: This paper introduces a stochastic model to maximize the probability of message delivery over ever-changing communication scenarios in tactical networks. Our model improves modern tactical systems implementing store-and-forward mechanisms organized in a hierarchy of layers for messages, IP packets and radios. The goal is to estimate the optimum redundancy for the user data-flow to overcome packet loss during changes in the link data rate, including disconnections. Experiments in a VHF network illustrate the nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Therefore, the minimum packet loss (P. Loss) observed in MG reached about 24 %, PRW with 4.8 % and GM reaching about 3.7 % of packet loss. Although RWP does not contain disconnections, we observed some packets loss of about 1.6 % which can be explained by the probability of packet loss increases in low data rates as calculated in [3] using experimental results with the same VHF radios.…”
Section: Experiments Over Model M B2mentioning
confidence: 67%
See 2 more Smart Citations
“…Therefore, the minimum packet loss (P. Loss) observed in MG reached about 24 %, PRW with 4.8 % and GM reaching about 3.7 % of packet loss. Although RWP does not contain disconnections, we observed some packets loss of about 1.6 % which can be explained by the probability of packet loss increases in low data rates as calculated in [3] using experimental results with the same VHF radios.…”
Section: Experiments Over Model M B2mentioning
confidence: 67%
“…The main question addressed in these investigations is how to guarantee that the models are creating enough variations in the communication scenarios to test the system's ability to handle unpredictable conditions including link disconnections and burst of messages. The investigation in [3] introduces a multi-layer stochastic model to compute the probability of message delivery. The goal is to maximize the probability of message delivery by adding redundancy to the user data flows.…”
Section: A Ever-changing Communication Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…After introducing TNT's mechanisms to create ever-changing user data flows and network conditions, the next step is to design a military system in order to test the platform over different scenarios as illustrated in Figure 1 (2). In previous investigations, we observed that the limited buffer size of military radios combined with the ever-changing network scenarios and user data flows (say message size and time distribution) results in buffer overflow [16], [38]. Therefore, we created a mechanism that can handle the radio buffer overflow by dynamically shaping the user data flow, and controlling the buffer usage within a given threshold.…”
Section: Military Systemsmentioning
confidence: 99%
“…Although RWP does not contain disconnections, we observed packet loss of about 1.6 %. The low packet loss happens because the probability of losing packets increases as the link data rate decreases, as calculated in [38] using experimental results with the same VHF radios.…”
Section: ) Trace Analysismentioning
confidence: 99%